Recovery of interest / financing charges due to prolongation in construction contract - Ng, Chee Kuang (2010)
It is a common occurrence for construction contracts to be delayed for one reason or another. This may be due to neutral event that beyond the control of the contracting parties or due to some act of prevention that cause by the employer or its authorized agent. In some circumstances, contractor requires more working capital and longer duration to accomplish the project is both increased and had to deployed over a longer period of time. As a result, when the project is prolonged, the contractor has to necessarily sustain cost of his working capital to ensure the contract can be fulfilled over the additional period of delay. Under the general principle of common law, financial loss in the form of interest charges is not recoverable without any express contractual or statutory provisions except claim under special damages. Since there are no express provision under the contract, can the additional interest/ financing charges incurred recoverable under ‘loss and/or expense’ provision? Hence, this research is conducted to reducing the uncertainty and difficulties in the event of recovery of interest/finance charges in the event the project is prolonged and additional working capital is required to sustain the project. This study classified as doctrinal research is an essentially a library-based study. It was found that interest which contractor has suffered during the period between the loss and/or expense being incurred and the making of an application for reimbursement is recoverable. It is also important to serve a notice to the contract administrator to inform the disruption of the regular progress of the work under loss and/or expense clause in the successful recovery of interest/financing charges.